What are the Risk Factors for ≥4500 g Macrosomia? - Elie NKWABONG; TANGHO Guilherme Roger NZALLI; Joseph Nelson FOMULU (Journal of Women's Reproductive Health, 2015)
Objective: To identify risk factors for ≥4500 g macrosomic babies given that maternal and neonatal complications of macrosomia increase with birth weight. Design: Cross sectional analytical study. Setting: The Yaoundé University Teaching Hospital and Central Maternity, Cameroon from October 1st, 2012 to June 30th, 2013. Population: 42 women who delivered ≥4500 g babies and 126 women who delivered babies of 4000 to <4500 g were recruited. Methods: Data were analysed using SPSS 18.0. Analyses included the student t-test and the Fisher exact test. The level of significance was P<0.05. Main outcome measures: Fetal sex and birth weight, gestational age at delivery, maternal age at delivery, parity, mother's pre-gestational body mass index (BMI), weight gain during pregnancy, father's BMI and past history of ≥4000 g macrosomia. Results: Main risk factors for ≥4500 g macrosomic babies were maternal weight gain of ≥16 kg (OR 4.2, 95%CI 2.0-8.9), maternal age ≥30 (OR 3.8, 95%CI 1.8-8.2), post term (OR 2.3, 95%CI 0.9-5.6), past history of ≥4000 g macrosomia (OR 1.9, 95%CI 0.9-4.1) and male sex (OR 1.3, 95%CI 0.6-2.8). Conclusion: To reduce the risk of ≥4500 g macrosomic babies, women at risk should make efforts to gain less than 16 kg bodyweight during pregnancies. Moreover, post term pregnancies should be avoided.